If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17w + -2 = 15w Reorder the terms: -2 + 17w = 15w Solving -2 + 17w = 15w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-15w' to each side of the equation. -2 + 17w + -15w = 15w + -15w Combine like terms: 17w + -15w = 2w -2 + 2w = 15w + -15w Combine like terms: 15w + -15w = 0 -2 + 2w = 0 Add '2' to each side of the equation. -2 + 2 + 2w = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 2w = 0 + 2 2w = 0 + 2 Combine like terms: 0 + 2 = 2 2w = 2 Divide each side by '2'. w = 1 Simplifying w = 1
| 16(x^2+11x+36)=0 | | 1.2=0.4y | | 5t-11=2t-5 | | -5y+5=-9y | | -17w-2=15w | | 0.7*2.4+16+4*2.4=27.28 | | x+3=2/9 | | 11/20= | | 2m+9m=33 | | 3.33=-3(9+n) | | 8x+1=7x-20 | | 50/100= | | 5x+3(10)=3.5(x+10) | | 20/1000= | | 4.3333(4.6666p-.25)=91.3611 | | 4y+18y=66 | | 8-4n=6n+2 | | -3y+9=-4y+3 | | 20/100= | | -10=-7+h | | -2x^3-2x^2=-40x | | 6x-6=9x-36 | | 20.2217(4.6666p-.25)=91.3611 | | 6x-6=9x-20 | | 6/10= | | .60= | | 20=-5x+2y | | 8-4n=6n | | 11x+16=2x+7 | | 37/50= | | 6z+24=6(z+4) | | 96=-4(6x-6) |